An investigation of cardiac vagal tone over time and its relation to vigilance performance: a growth curve modeling approach - McGarry, Shannon P. D.; Neilson, Brittany N.; Brown, Noelle L.; Strong, Kaylin D.; Greenlee, Eric T.; Klein, Martina I.; Coyne, Joseph T. (Frontiers in Neuroergonomics, 2023)
Introduction Research over the last couple of decades has demonstrated a relationship between psychophysiological measures, specifically cardiac functions, and cognitive performance. Regulation of the cardiac system under parasympathetic control is commonly referred to as cardiac vagal tone and is associated with the regulation of cognitive and socioemotional states. The goal of the current study was to capture the dynamic relationship between cardiac vagal tone and performance in a vigilance task. Method/Results We implemented a longitudinal growth curve modeling approach which unveiled a relationship between cardiac vagal tone and vigilance that was non-monotonic and dependent upon each person. Discussion The findings suggest that cardiac vagal tone may be a process-based physiological measure that further explains how the vigilance decrement manifests over time and differs across individuals. This contributes to our understanding of vigilance by modeling individual differences in cardiac vagal tone changes that occur over the course of the vigilance task.